What Love Is Not: Lessons from Martin Luther King, Jr. (12th November 2019) - Lloyd, Vincent
Abstract: Focusing on the concept and practice of love sheds light on Martin Luther King, Jr.'s negative political theology. King was fundamentally concerned with what love is not, and it is this negation that colors his political vision. I do not take King's political theology to be either primarily derivative of American liberal Protestantism or primarily derivative of folk African American religion, or of some syncretism of these. Rather, I take King to be participating in a tradition of negative theology that pairs the critique of idolatry with attention outward and inward, to the marginalized and to spiritual life.